1981
DOI: 10.1159/000182161
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII Activity in Chronic Renal Disease

Abstract: F VIII coagulant, F VHI-related antigen and F VIII ristocetin cofactor activity were significantly increased in 68 patients with various chronic renal diseases. All three F VIII functions correlated generally well with each other. A striking relationship between some F VIII activities and serum creatinine was detectable in patients with glomerulonephritis and kidney transplants, with mild or moderate renal insufficiency. This correlation was no longer present in terminal renal failure. The results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…Our studies confirm the finding of others [20,25,29,30] that patients with chronic renal failure have normal or high plasma levels of factor VIII activities. Although DDAVP infusion tended to further elevate these levels, only FVIIIRCOF was significantly elevated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our studies confirm the finding of others [20,25,29,30] that patients with chronic renal failure have normal or high plasma levels of factor VIII activities. Although DDAVP infusion tended to further elevate these levels, only FVIIIRCOF was significantly elevated.…”
Section: Discussionsupporting
confidence: 92%
“…Were this the case, the logical therapeutic manoeuvre would be cryoprecipitate or DDAVP infusion. However, this observation has not been confirmed by the majority of investigators, and it would now appear that the activity of factor VIII von Willebrand's factor is normal or even elevated in uraemic patients [20,25,29,30]. Moreover, normal factor VIII related protein is immunologically detectable in the vascular intima of patients with chronic renal failure who have prolonged bleeding times [23].…”
Section: Discussionmentioning
confidence: 98%
“…Increasing factor VIlI:c has obviously no great importance to the hemo stasis. Previously it has been reported that factor VIILc acts as an acute-phase reactant in uremic patients [18],…”
Section: Discussionmentioning
confidence: 99%
“…Although factor VIII-von Willebrand's levels appear to be normal or even elevated in the presence of renal insufficiency [8][9][10], an increase in the circulating levels of larger mul timeric forms of this factor following DDAVP infusion has recently been noted [4], Thus, it is tempting to spec ulate that DDAVP exerted its beneficial effect on the pro longed bleeding time and clinical hemorrhage in the cases presented via alteration of factor VIII-von Willebrand's factor activity. Further support of this hypothesis and the possibility that factor VIII-von Willebrand's factor activ ity may be at least partly responsible for the hemostatic defect of uremia is provided by the report of Janson et al [11].…”
Section: Discussionmentioning
confidence: 99%